Cholestasis impaired spatial and non-spatial novelty detection in mice - Nasehi, Maryam; Hesami Tackallou, Saeed; Hasani, Iman; Nasehi, Mohammad (Archives of Advances in Biosciences, 2013)
Bile duct ligation (BDL) is shown to induce cholestasis-related liver function impairments as well as consequent cognitive dysfunctions (i.e. impaired learning and memory formation). This study investigates the effects of cholestasis (14, 21 and 28 days post bile duct ligation) on spatial and non-spatial novelty detection, using a non-associative task. Male mice weighing 30-35 g were used. Cholestasis was induced by ligation of the main bile duct using two ligatures and transecting the duct at the midpoint between them. Open field paradigm was employed to assess the spatial and non-spatial memories retention. Our data showed that cholestasis (28 days after bile duct ligation) decrease and increased duration time of displace and non-displace objects respectively, indicating spatial memory deficit. Moreover, this intervention (28 days after bile duct ligation) decreased and did not alter duration time of substitute and non-substitute objects respectively, suggesting non-spatial memory deficit. Moreover, the data postulated that 14 and 21 days post bile duct ligation both spatial and non-spatial memories did not alter. Our results suggested that cholestasis (28 but not 14 and 21 days post bile duct ligation) impaired spatial and non-spatial memory in the mice.